Atypical teratoid/rhabdoid tumor of the sellar region in adult women: Is it a sex-related disease?. (March 2018) - Nishikawa, Akihiro; Ogiwara, Toshihiro; Nagm, Alhusain; Sano, Kenji; Okada, Maki; Chiba, Akihiro; Agata, Masahiro; Kaneko, Tomoki; Tamada, Hisashi; Uehara, Takeshi; Hongo, Kazuhiro
Highlights: Autopsy findings could prove the clinical characteristics of rare pituitary AT/RT. Pituitary AT/RT might be a sex-related disease. AT/RT should be considered in middle-aged women with aggressive pituitary tumor. Early making diagnosis and treatment might improve outcomes of pituitary AT/RT. Abstract: Atypical teratoid/rhabdoid tumor (AT/RT) is a highly malignant embryonal tumor in children and a rare entity. Although adult AT/RT is extremely rare, some cases of adult-onset AT/RT in the sellar region have been described. Here, we report an adult patient with AT/RT of the sellar region in whom it was difficult to make a definitive diagnosis and the clinical course was aggressive. This is the first report of autopsy findings that could confirm the clinical characteristics of this rare unresolved pathology, and will contribute to the improvement of prognosis. In addition, a literature review was performed to clarify this exceptionally rare condition. Interestingly, all reported adult patients with sellar AT/RT, along with the present case, were female. This raises the possibility of its being a sex-related disease. However, further studies are required to come to a definitive conclusion.